FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA SISA MAKANAN NARAPIDANA (Studi di Lembaga Pemasyarakatan Klas I Semarang) - ENI KURNIAWATI; Siti Fatimah Pradigdo; M. Zen Rahfiludin (Jurnal Kesehatan Masyarakat (Undip), 2016)
A prisoner has the right to get adequate nutritional food. The success of food service related to plate waste presences. Plate waste is more than 25% showed that feeding was not optimal. The purpose of this study was to analyze the factors associated with plate waste of prisoners in Correctional Institution Class I Semarang. This study used analytic observational with the cross-sectional approach. The sampling technique used in this study is purposive sampling amounted to 65 prisoners. Data collected through interviews and calculation of food waste using food weighing for three days. The results showed that almost prisoners had a lot of plate waste (86,2%), the most plate waste is the staple food (46,1%), vegetables (53,1%), and vegetable side dishes (33,3%). The prisoners represented that the menu was not variety accounted for 50,8%, the food appearance was interesting (50,8%), that food tastes are delicious (53,8%), and most of the prisoners consumed food from outside twice a week (49,2%). The highest plate waste in the morning accounted for 45,8%. Based on Spearman Rank Test, the factors related to plate waste is food tastes (p-value = 0,044 and the correlation coefficient (ρ) = -0,251) and food from outside (p-value = 0,001 and the correlation coefficient (ρ) = 0,602) and factors unrelated is menu variations (p-value = 0,554) and the food appearance (p-value = 0,914). The correctional institution suggests to evaluate the standard portion, especially in the morning and keep improving the food tastes.